1987
DOI: 10.1113/jphysiol.1987.sp016683
|View full text |Cite
|
Sign up to set email alerts
|

The effect of splanchnic nerve section on the sensitivity of the adrenal cortex to adrenocorticotrophin in the calf.

Abstract: SUMMARY1. Adrenal cortical responses to adrenocorticotrophin (ACTH) in conscious 2-6-week-old calves, in which both splanchnic nerves had been cut at least 7 days previously, were compared with those of normal calves of the same age in order to discover whether splanchnic nerve section affects the sensitivity of the adrenal cortex to the trophin.2. In one series of experiments an increase in the release of endogenous ACTH was elicited by an i.v. infusion of noradrenaline (333 ng min-' kg-' for 10 min) and in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 20 publications
(20 reference statements)
3
30
0
1
Order By: Relevance
“…This concept of adrenal cortical control by adrenal nerves is similar to that demonstrated by Edwards and coworkers (14,15). In the fetal sheep, it is possible that the splanchnic innervation of the adrenal cortex dynamically regulates adrenal sensitivity to ACTH.…”
Section: Discussionsupporting
confidence: 73%
“…This concept of adrenal cortical control by adrenal nerves is similar to that demonstrated by Edwards and coworkers (14,15). In the fetal sheep, it is possible that the splanchnic innervation of the adrenal cortex dynamically regulates adrenal sensitivity to ACTH.…”
Section: Discussionsupporting
confidence: 73%
“…Only relatively recently has the importance of the innervation of the gland on adrenocortical secretion been determined. Thus, Edwards and Jones (38) using conscious, hypophysectomized calves showed that stimulation of the splanchnic input to the adrenal gland doubled, whereas splanchnic denervation halved (39), the output of cortisol in response to an exogenous infusion of ACTH. In the fetus, similar neural mechanisms operate in the control of stimulated adrenocortical secretion, because functional innervation of the ovine fetal adrenal gland is present by the final third of gestation (40,41), and Myers et al (42) showed that splanchnic nerve section in the ovine fetus had no effect on basal plasma cortisol concentration but significantly attenuated the cortisol increment during acute hypotensive stress.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the greatly increased fat deposition in TG animals (after the age of 4 months), especially accumulated in adipose tissue (Pepin et al, 1992a), may be attributable to the decreased sympathetic nervous activity rather than to GR dysf unction. Because sympathetic activity enhances ACTH-dependent cort secretion from the adrenal gland (Edwards and Jones, 1987;Engeland and Gann, 1989;Bornstein et al, 1990;Jasper and Engeland, 1994;Dijkstra et al, 1996), the decreased sensitivity of the adrenal gland for ACTH may be a consequence of the reduced sympathetic outflow in TG mice. Thus, it is important to note that the phenotype of the GR defunct mice appears for a large part to be determined by the reduced hypothalamic CRH activity.…”
Section: Discussionmentioning
confidence: 99%